A statistical study of factors affecting natural biovinegar fermentation from pineapple peel waste - Yashini, Selvanathan; Nasratun, Masngut (IOP Publishing, 2021)
The objective of this work was to screen and evaluate the significant parameter which affected the natural fermentation of pineapple biovinegar. In this work, peel waste from local breed pineapple (Royal Pepina) was fermented naturally to produce an aromatic biovinegar. Full factorial design of Design Expert® was used to develop a random experimental run in which six parameters were screened off. They were the fermentation temperature (27 – 50 °C), fermentation time (5 – 28 days), fermentation condition (anaerobic and aerobic), the addition of glucose (0 – 7 %), the addition of yeast (0 – 0.3 %), and peel waste condition (slurry & juice). Three parameters were identified as significant factors, which were the condition of fermentation, fermentation temperature, and addition of glucose. The ANOVA of the model was statistically significant with R2 of 0.9948. The pineapple biovinegar produced in this work contained 3.18 % reducing sugar, 1.03 % ethanol, 3.03 % acid, 0.61 % acetic acid, 1.43 mg equi. AA/100mL ascorbic acid, pH of 3.16, 4.0 % sucrose, 8.0 °Brix total soluble solid, and 82.06 % DPPH free-radical scavenging activity of antioxidant in biovinegar. This result stood second highest after apple cider biovinegar when compared to commercially available biovinegar.